Integrated environmental education physics project to enhance student creativity - Nurita Apridiana Lestari; Fajaria Meli Susanti; Madlazim Madlazim; Eko Hariyono; Rizki Fitri Rahima Uulaa (Universitas PGRI Kanjuruhan Malang, 2024)
This study aims to describe the results of research on physics education integrated with environmental issues, especially related to climate change, through literature review and its implementation in schools. The aspects observed include the feasibility, effectiveness, and student responses to the implementation of integrated physics learning with environmental education related to climate change to enhance creativity. The research method used was quantitative research with a true experimental design involving pretest and posttest control groups. The subjects of the study were science students in public secondary schools in Jombang, divided into experimental and control groups. The research data were processed using observation sheets for the feasibility of learning, prerequisite tests including tests for data normality and homogeneity, paired t-tests, two-tailed t-tests, one-tailed t-tests, n-gain tests, effect size, and student response questionnaires. Based on the research findings, it can be concluded that (1) there is a significant difference in students' creativity before and after the implementation of integrated physics learning with environmental education related to climate change, with the experimental group experiencing a higher increase compared to the control group, indicating the effectiveness of integrated physics learning with environmental education. (2) Student responses after the implementation of integrated physics learning with environmental education related to climate change were categorized as excellent. Therefore, as an initial study, it can be stated that climate change education can be implemented in the form of project performance and has an impact on student creativity.